Analysis of The Influence of Digital Payment Process, Quality of Application, and Online Service on Repurchase Intention of Online Shopping Platform Customers - Maksimilianus Gai, Ardiyanto; Zakaria, Muhammad; Harsono, Iwan; Widia Nurdiani, Tanti; Razak Munir, Abdul (SEULANGA SYSTEM PUBLISHER, 2024)
In order to understand how customer satisfaction is affected by convenience, transaction process, system quality, content reliability, and customer service, as well as how this affects customer complaints and repurchase intentions, these factors will be examined in this study. We employed the descriptive research method in conjunction with conclusive research in this study. For this study, a cross-sectional design was employed. A questionnaire was used in this study's data collection process. Those who have utilized the mobile application and filed complaints with customer support make up the demographic under investigation. With a sample size of 100 participants, judgmental sampling was used in this study. The structural equation model method will be used to examine the data in this study. The data analysis's findings highlight a number of significant conclusions. Firstly, there is no evidence that convenience significantly affects customer happiness. Second, client happiness is greatly enhanced by the transaction procedure. Third, customer satisfaction is positively impacted by system quality as well. Fourth, customer happiness is positively impacted by content reliability as well. Fifth, customer satisfaction is positively impacted by customer service. Sixth, complaints from customers are negatively impacted by consumer satisfaction. Seventh, the propensity to repurchase is positively impacted by customer satisfaction. Eighthly, however, there is a negative correlation between consumer satisfaction and propensity to repurchase. These results, notwithstanding certain discrepancies, imply that factors other than customers' degree of satisfaction might also affect their intention to make another purchase.